Using different surgical techniques and ideas to reduce post-operative adhesion formation: a systematic review and meta-analysis - Rani, Rekha; Singh, Shikha; ., Urvashi; Garg, Ruchika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Adhesion development is the most common sequelae of intra-abdominal and pelvic surgery. Using a good surgical technique is advocated as a first step in preventing adhesions. However, the evidence for different surgical techniques to reduce adhesion formation needs confirmation. This review contributed to the growing knowledge pool by elucidating factors that potentially predispose to the development of adhesions. A literature search was performed using the PubMed database for all relevant English language articles and were reviewed with particular attention to predisposing factors to post-operative adhesion development. In addition, the reference lists of each article were reviewed to identify additional relevant articles. Various factors have been shown to directly increase the risk of post-operative adhesion development; namely, certain genetic polymorphisms in the interleukin-1 receptor antagonist, increased estrogen exposure, and endometriosis. There were 28 papers with 27 studies included for a systematic review. Of these, 17 studies were eligible for meta-analysis and 11 for qualitative assessment only. None of the techniques that were compared significantly reduced the incidence of adhesive small bowel obstruction. In a small low-quality trial, the pregnancy rate increased after subserous fixation of suture knots. However, the incidence of adhesions was lower after laparoscopic compared with open surgery (relative risk (RR): 0.14; 95% confidence interval (CI): 0.03-0.61) and when the peritoneum was not closed (RR: 0.36; 95% CI: 0.21-0.63). None of the specific techniques that were compared reduced the two main adhesion-related clinical outcomes, small bowel obstruction and infertility.